2018
DOI: 10.1186/s13049-018-0499-9
|View full text |Cite
|
Sign up to set email alerts
|

Temporal phenotyping of circulating microparticles after trauma: a prospective cohort study

Abstract: BackgroundAfter severe polytrauma the dynamic process of coagulation may deteriorate towards a trauma-induced coagulopathy (TIC) promoting a dramatic increase in morbidity and mortality. Recent evidence suggests that microparticles (MPs) play a pivotal role at the interface between cellular and plasmatic coagulation systems. However, the impact of MPs on functional coagulation has not been clarified yet in the setting of traumatic injuries. We assessed the temporal patterns of circulating MP concentrations inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 27 publications
7
34
1
Order By: Relevance
“…As recently published by our group, there is a positive correlation between injury severity and MP concentration after trauma likely reaching high quantities inducing procoagulative effects [16]. Our in vitro experimental setup indicates that under LT conditions MP promote procoagulative function by different pathways based on their cellular origin.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…As recently published by our group, there is a positive correlation between injury severity and MP concentration after trauma likely reaching high quantities inducing procoagulative effects [16]. Our in vitro experimental setup indicates that under LT conditions MP promote procoagulative function by different pathways based on their cellular origin.…”
Section: Discussionsupporting
confidence: 73%
“…Special emphasis was given on the analysis of selected MP on blood coagulation with particular focus on PDMP and EDMP. Both MP subtypes had been reported to be released in high quantities in patients who sustained major traumatic injuries indicating that these particles might be involved in regulating blood coagulation after trauma [16,17,21,22]. With this study we demonstrated for the rst time a divergent mechanism of action on coagulation originating from MP with different parental cells.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…These microparticles of platelet cell membrane are procoagulant, 58,59 and their levels in circulation increase after injury. 60 In one study, patients with only modest increases in the PMP level had a higher incidence of coagulopathy and higher blood transfusion requirement, 61 though another large study found no clear association. 62 These heterogeneous findings could arise from the existence of multiple PMP subpopulations with differing phenotypic effects.…”
Section: Novel Therapeutic Approaches To Platelet Dysfunctionmentioning
confidence: 98%
“…Special emphasis was given to the analysis of selected MP on blood coagulation with a particular focus on PDMP and EDMP. Both MP subtypes had been reported to be released in high quantities in patients who sustained major traumatic injuries indicating that these particles might be involved in regulating blood coagulation after trauma [19,25,31,32]. With this study we demonstrated for the rst time a divergent mechanism of action on coagulation originating from MP with different parental cells.…”
Section: Discussionmentioning
confidence: 60%